2017
DOI: 10.1007/s11249-017-0813-0
|View full text |Cite
|
Sign up to set email alerts
|

Positron Annihilation and Complementary Studies of Stainless Steel Exposed to Sandblasting at Different Angles

Abstract: Defect studies in subsurface zone in stainless steel 304 AISI samples exposed to sandblasting were performed using positron annihilation spectroscopy techniques. Samples were sandblasted with a different impact angle. Conventional experiments based on positrons emitted directly from the radioactive source allowed us to detect vacancies on the dislocation edges in all samples; however, the total depths of subsurface zones depended strictly on the impact angle, i.e., 35 lm for impact angle of 90°and about 12 lm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 24 publications
(24 reference statements)
2
14
0
Order By: Relevance
“…4a. It is worth noticing that VEP results obtained for niobium are significantly different than those obtained in similar conditions for Cu [13], Fe [28], or stainless steel [14,27]. Nevertheless, they are in qualitative agreement with the results obtained by Gu et al [29].…”
Section: Positron Beam Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…4a. It is worth noticing that VEP results obtained for niobium are significantly different than those obtained in similar conditions for Cu [13], Fe [28], or stainless steel [14,27]. Nevertheless, they are in qualitative agreement with the results obtained by Gu et al [29].…”
Section: Positron Beam Resultssupporting
confidence: 83%
“…Our recent studies of subsurface zones created during dry sliding in Ti [10] and Zr [11] showed that they exhibited quite different defect depth distribution than in metals that have tribological application such as Fe [12], Cu [13], stainless steel [14]. We believe that studies of subsurface zone in metals, which are not used in tribojunctions can expand our knowledge about defects generation during sliding.…”
Section: Introductionmentioning
confidence: 90%
“…These lifetimes are comparable or even slightly greater to those observed in the stainless steel subjected to dry sliding [6], while sandblasting [7] has effect similar to the one observed in the grinded sample. The data on the mean lifetimes and Vickers hardness numbers measured with changing E, j and 1/D for shot peened samples are compiled in τ mean -HV coordinate system in Fig.…”
Section: Resultssupporting
confidence: 74%
“…Our previous research has shown that unalloyed, bearing and carburizing steels as well as aluminum and titanium alloys, which were subjected to SP, can be successfully investigated by PALS [4,5]. Also the PALS studies of the surface layer of the stainless steels treated by dry sliding [6] and sandblasting [7] allow to expect that this technique is suitable for similar steels.…”
Section: Introductionmentioning
confidence: 99%
“…During the years 2014-2018 about 80 runs for PAS were performed at the LEPTA facility. The samples of irradiated metals [7][8][9][10][11] as well as subjected to a surface treatment [12,13] were subsequently investigated by the DBAL PAS method.…”
Section: Studies Using Dbal Pas Methods At Lepta Facilitymentioning
confidence: 99%